The membrane-raft protein Flotillin-1 is essential in dopamine neurons for amphetamine-induced behavior in Drosophila - Pizzo, Andrea B. (2012)
The dopamine transporter (DAT) is the primary molecular target responsible for the rewarding properties of the psychostimulants amphetamine (AMPH) and cocaine. AMPH increases extracellular dopamine (DA) by promoting its nonexocytotic release via DAT-mediated efflux. Previous studies in heterologous cells have shown that phosphorylation of the amino terminus of DAT is required for AMPH-induced DA efflux but not for DA uptake. However, the identity of many of the modulatory proteins and the molecular mechanisms that coordinate efflux and the ensuing behavioral effects remain poorly defined. Here we establish a robust assay for AMPH-induced hyperlocomotion in Drosophila melanogaster larvae. Using a variety of genetic and pharmacological approaches we demonstrate that this behavioral response is dependent on DA and on DAT and its phosphorylation. We also show that methylphenidate (MPH), which competitively inhibits DA uptake but does not induce DAT-mediated DA efflux, also leads to DAT-dependent hyperlocomotion, but this response is independent of DAT phosphorylation. Moreover, we demonstrate that the membrane raft protein Flotillin1 is required for AMPH-induced but not MPH-induced hyperlocomotion. These results are the first evidence of a role for a raft protein in an AMPH-mediated behavior. Thus, using our assay we are able to translate molecular and cellular findings to a behavioral level and to differentiate in vivo the distinct mechanisms of two psychostimulants.